A Radioactivity-Based Assay for Screening Human m6A-RNA Methyltransferase, METTL3-METTL14 Complex, and Demethylase ALKBH5. (March 2016) - Li, Fengling; Kennedy, Steven; Hajian, Taraneh; Gibson, Elisa; Seitova, Alma; Xu, Chao; Arrowsmith, Cheryl H.; Vedadi, Masoud
N 6 -methyladenosine (m 6 A) is the most common reversible internal modification in mammalian RNA. Changes in m 6 A levels have been implicated in a variety of cellular processes, including nuclear RNA export, control of protein translation, and protein splicing, and they have been linked to obesity, cancer, and other human diseases. METTL3 and METTL14 are N 6 -adenosine methyltransferases that work more efficiently in a stable METTL3-METTL14 heterodimer complex (METTL3-14). ALKBH5 is an m 6 A-RNA demethylase that belongs to the AlkB family of dioxygenases. We report the development of radioactivity-based assays for kinetic characterization of m 6 A-RNA modifications by METTL3-14 complex and ALKBH5 and provide optimal assay conditions suitable for screening for ligands in a 384-well format with Z′ factors of 0.78 and 0.77, respectively.